Three-dimensional hierarchical nanoporous copper via direct ink writing and dealloying. (1st March 2020) - Mooraj, Shahryar; Welborn, Samuel S.; Jiang, Shuyang; Peng, Siyuan; Fu, Jintao; Baker, Sarah; Duoss, Eric B.; Zhu, Cheng; Detsi, Eric; Chen, Wen
Abstract: Three-dimensional (3D) hierarchical nanoporous Cu (3DHNP-Cu) is synthesized using a combination of direct ink writing (DIW) based 3D printing, thermal sintering, and chemical dealloying of Mn–Cu alloys. Through tuning processing conditions such as ink composition and cooling rate (after sintering), with consideration of Mn loss during sintering, 3DHNP-Cu with fully bicontinuous nanostructures and negligible residual Mn can be produced after dealloying. The 3DHNP-Cu is comprised of structural features that span seven orders of magnitude, where DIW digitally controls macroscale porous features, thermal sintering and degradation of the binding polymer determines microscale porous features, and dealloying gives rise to nanoscale pores. Graphical abstract: Image, graphical abstract